MENJUNJUNG TINGGI ISLAM AGAMA KASIH SAYANG DAN CINTA KASIH DALAM DIMENSI SUFISME - Muhamad Basyrul Muvid (Institut Dirosat Islamiyah Al-Amien Prenduan, 2021)
This paper seeks to explore in detail about Islam as a religion of compassion and love in the wrap of Sufism. This research is a literature that takes its main source from various literature related to the above theme. The results of the analysis state that Islam is not in the least ordered to be anarchic and intolerant, but instead Islam teaches and educates people to be gentle, appreciative, kind, compassionate to all creatures of Allah as Allah Himself is kind to His creation. This is in accordance with the teachings of Sufism (Sufistic Islam), which confirms noble morality, moral hygiene, soul and mind that are very far from negative elements and all bad deeds, for that the idea of Islam as a religion of mercy and love is very important especially strengthened by the Sufistic dimension.